Fabrication of Topical Pluronic Lecithin Organogel Containing Immunomodulatory Drug for Site-Specific Drug Delivery - Gohil, Dipti; Shah, Miten; Shah, Nirmal; Maheshwari, Rajesh A. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Rheumatoid Arthritis is an Autoimmune disease, can be categorized by painful joints with limited treatment option. An Oral administration of Leflunomide for longer duration might lead to the Liver Toxicity. Hence, site specific delivery of an Immunomodulatory drug can be proposed for symptomatic relief of pain. Materials and Methods: Present study is focused on the formulation of Leflunomide using Pluronic Lecithin Organogel as a platform to enhance permeation through skin, bypass hepatic metabolism and to achieve local action. Prepared formulation was optimized by using 32 full factorial design and characterized for various parameters such as viscosity, physical form, pH, drug content, Spreadability, in vitro drug release profile and stability. Results: Optimized formulation of organogel showed (%) drug release up to 8 hr. Further, anti-inflammatory activity and Histopathology study of developed formulation confirmed safe and effective use for topical application. Conclusion: The study concluded that developed formulation is effective for topical treatment of Rheumatoid Arthritis. The study would be extended to assess the clinical application of preparation.
Keywords: Pluronic Lecithin Organogel; 32 full factorial design; Topical application; Rheological; study; Anti-inflammatory activity; Histopathology study